2012
DOI: 10.1029/2011pa002237
|View full text |Cite
|
Sign up to set email alerts
|

Silicic acid biogeochemistry in the Gulf of California: Insights from sedimentary Si isotopes

Abstract: [1] Iron is considered to play a large role in the cycling of Si in Fe-limited regions of the ocean, but little is known about its role in Si biogeochemistry outside these areas. Here, we present published sediment trap data, new nutrient profiles and high resolution sedimentary records (Si isotopes, Biogenic silica%, N% and C%) from the Gulf of California, a non-Fe-limited region, to investigate the history of Si cycling in this highly productive basin. Modern nutrient profiles show that silicic acid in subsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 89 publications
(149 reference statements)
1
66
0
1
Order By: Relevance
“…Coherent TOC and Si/Ti maxima are observed (e.g., 1130 and 1300 CE), yet negative correlations between Si/Ti and TOC are shown during intervals of low Si/Ti, during which TOC remains relatively stable (Figures b and e). Anticorrelations between TOC and biogenic silica have also been recorded in the Gulf of California, where biogenic silica is the primary biogenic sediment component (Pichevin et al, ; Thunell, ). Previous studies have related this inverse relationship to either Fe limitation (Firme et al, ) and/or enhanced silica preservation during strong coastal upwelling events due to silica supersaturation in porewaters (Pichevin et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Coherent TOC and Si/Ti maxima are observed (e.g., 1130 and 1300 CE), yet negative correlations between Si/Ti and TOC are shown during intervals of low Si/Ti, during which TOC remains relatively stable (Figures b and e). Anticorrelations between TOC and biogenic silica have also been recorded in the Gulf of California, where biogenic silica is the primary biogenic sediment component (Pichevin et al, ; Thunell, ). Previous studies have related this inverse relationship to either Fe limitation (Firme et al, ) and/or enhanced silica preservation during strong coastal upwelling events due to silica supersaturation in porewaters (Pichevin et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Estos valores de las razones N:P y Si:N se encuentran en el intervalo de valores documentados previamente para el GC. Por ejemplo, Torres-Valdés (2000) estimó razones N:P que variaron de 12.7 en invierno a 9.3 en verano, mientras que Pichevin et al (2012) registraron una razón Si:N >1.8 y la atribuyeron como característica del GC.…”
Section: Efecto De Los Procesos Biológicos Sobre La Distribución De Lunclassified
“…These values are within the range of values previously reported for the GC. For example, Torres-Valdés (2000) estimated N:P ratios varying between 12.7 in winter and 9.3 in summer, while Pichevin et al (2012) reported a Si:N ratio of >1.8 as characteristic for the GC. zona continental.…”
Section: Effect Of Biological Processes On the Distribution Of Nutriementioning
confidence: 99%
“…Intense productivity could have led to total Fe utilisation during upwelling events thus to transient Fe limitation at the end of an upwelling event (Hutchins and Bruland, 1998;Firme et al, 2003). Iron limitation can lead to reduced cellular organic matter production and increased silicification (high cellular Si : C and Si / N ratio) of diatoms (Baines et al, 2010Brzezinski et al, 2011), high Si:C ratio in sinking biogenic particles, high opal flux (Hutchins and Bruland, 1998;Firme et al, 2003;Pichevin et al, 2012), and better frustule preservation in sediments. This scenario is consistent with the unvarying TOC contents in MD08 core across stadial/interstadials DO intervals of MIS5 (Fig.…”
Section: High Biogenic Opal Content In Mis5 Sedimentsmentioning
confidence: 99%